Microplastics Formation, Distribution, Impact, and Mitigation Strategy: A Review - Yohanna Indriyani; Rustam Efendi (Warmadewa University Press, 2025)
The use of plastics in this modern era has become an inevitable necessity, due to its favorable properties such as lightweight, corrosion resistance, good plasticity and flexibility, thermal and electrical insulation, and low cost. Unfortunately, the production and use of plastics, which is increasing year by year, is being realized more as a hazard to the environment and living beings, especially due to microplastic contamination. Microplastics, defined as plastics less than 5 mm in size and the result of abiotic and biotic degradation of plastic polymers, have been reported to pollute various aquatic and terrestrial ecosystems, and are found in various plants, animals, and human tissues, as well as biological samples. The global concern for microplastic contamination makes it important to have an understanding of how microplastics are formed in the environment and what mitigation strategies can be done. This paper reviews recent articles on issues related to microplastics from the Scopus database, Google Scholars, and other web sources from the period covering 2017-2024, and focuses on understanding the formation of microplastics in the environment, microplastics in aquatic and terrestrial ecosystems (sources, distribution, and environmental impacts), the impacts of microplastics on living organisms (plants, fauna, and human health), and microplastics mitigation strategies.